No Prices No Games! Four Economic Models - Michael Richter (Open Book Publishers, 2024)
While current economic theory focuses on prices and games, this book models economic settings where harmony is established through one of the following societal conventions: A power relation according to which stronger agents are able to force weaker ones to do things against their will. A norm that categorizes actions as permissible or forbidden. A status relation over alternatives which limits each agent's choices. Systematic biases in agents' preferences. These four conventions are analysed using simple and mathematically straightforward models, without any pretensions regarding direct applied usefulness. While we do not advocate for the adoption of any of these conventions specifically – we do advocate that when modelling an economic situation, alternative equilibrium notions should be considered, rather than automatically reaching for the familiar approaches of prices or games.
Keywords: 330; Economic Theory; Models; Prices; Games; Agents; Equilibrium